Mixture finely grounded into powder form - Mumbai Archive Project Team (Jio Institute, 2024)
The raw ingredients are mixed at the mill. The mixture is finely ground into powder form. A single kg of masala takes about 4–5 hours of pounding and grinding to blend the powder effectively.